2019
DOI: 10.1101/665067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anatomical meniscus construct with zone specific biochemical composition and structural organization

Abstract: A PCL/hydrogel construct that would mimic the structural organization, biochemistry and anatomy of meniscus was engineered. The compressive (380 ± 40 kPa) and tensile modulus (18.2 ± 0.9 MPa) of the PCL scaffolds were increased significantly when constructs were printed with a shifted design and circumferential strands mimicking the collagen organization in native tissue (p<0.05). Gene expression of human fibrochondrocytes in agarose (Ag), gelatin methacrylate (GelMA), and GelMA-Ag hydrogels was significantly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Studies have proposed that the platelet concentration most conducive to tissue healing is 1.5–3.0×10 6 /μL, which is about 3-fold to 8-fold higher than the physiological concentration of platelets in whole blood [16]. Furthermore, recent studies have indicated that the immediate use of platelets after the inflammatory phase has the greatest effects on tissue healing [17]. It is suggested that the early use of PRP without delay is more important than the number of platelets it contains [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proposed that the platelet concentration most conducive to tissue healing is 1.5–3.0×10 6 /μL, which is about 3-fold to 8-fold higher than the physiological concentration of platelets in whole blood [16]. Furthermore, recent studies have indicated that the immediate use of platelets after the inflammatory phase has the greatest effects on tissue healing [17]. It is suggested that the early use of PRP without delay is more important than the number of platelets it contains [18].…”
Section: Discussionmentioning
confidence: 99%
“…3D fabrication technologies for zonal fibrocartilage TE currently under investigation rely on (i) mimicry of the arrangement of collagen fibers and bundles 25,59,60,[82][83][84][85][86][87][88][89][90] , (ii) zonedependent biomaterial composition [91][92][93] and (iii) different degree of porosity 91,92,94 .…”
Section: Recent Advances In Meniscal Zonal Reconstructionmentioning
confidence: 99%
“…It is well known the use of hydrogels for producing tissue engineering scaffolds for cartilaginous tissues, because of their biocompatibility, bioactivity, and structural similarity to the ECM . The investigated hydrogel blends show improved performance over individual polymers and as result their range of applications has been extended.…”
Section: Agarosementioning
confidence: 99%
“…Bilgen's group reported new materials for potential regeneration of meniscus which were tested under dynamic compression. They evaluated a series of materials like fibro‐chondrocyte‐seeded agarose, methacrylated gelatin (GelMA), methacrylated hyaluronic acid (MeHA) and GelMA‐MeHA blend hydrogels, and 3D printed poly(caprolactone) (PCL) scaffolds . The investigation showed higher levels of ECM components produced by the cell‐carrying hydrogels after 35‐day incubation than the 3D printed PCL, proving their higher potential for meniscal regeneration and the capacity of the fibro‐chondrocytes to be directed to proliferate or produce cartilaginous or fibro‐cartilaginous ECM.…”
Section: Agarosementioning
confidence: 99%
See 1 more Smart Citation